Deep learning and computer chess (part 2) - Ngoh, Guang Wei (Nanyang Technological University, 2020)
Monte Carlo Tree Search (MCTS) is a probabilistic algorithm that has gained traction in recent years. MCTS uses lightweight random simulations to selectively grow a game tree and has experienced success in domains with vast search spaces, such as chess.